Changes of Serum Melatonin, Interleukin-6, Homocysteine, and Complement C3 and C4 Levels in Patients With Depression - Tao, Huai; Chen, Xia; Zhou, Hongfei; Fu, Jinhua; Yu, Qi; Liu, Yong (Frontiers in Psychology, 2020)
Objectives Cytokine activation and low complement levels are common in depression patients. This study is aimed at investigating the clinical significance of changes in serum concentrations of melatonin (MT), interleukin-6 (IL-6), homocysteine (hcy), and complement C3 and C4 in depression patients and relationships of them with depression activity. Methods A total of 95 depression patients, including first-episode group (n = 43) and recurrent group (n = 52), and 45 age- and gender-matched healthy controls (HC) were recruited. Serum levels of MT, IL-6, hcy, C3, and C4 in all samples were measured by using enzyme-linked immunosorbent assay (ELISA), chemiluminescence method, enzyme circulation method, and immuno-scatter turbidimetric assay, respectively. Results The serum MT, IL-6, and hcy levels in the first-episode group (113.08 ± 5.06 pg/ml, 2.06 ± 0.12 ng/L, and 13.87 ± 0.45 μmol/L), and recurrent group (117.63 ± 4.63 pg/ml, 2.20 ± 0.12 ng/L, and 13.61 ± 0.46 μmol/L) were significantly higher than those in the control group (89.50 ± 5.10 pg/ml, 1.57 ± 0.06 ng/L, and 11.34 ± 0.40 μmol/L). The serum levels of C3 in the first-episode group (0.95 ± 0.02 ng/L) were significantly lower than those in the recurrent group (1.05 ± 0.03 ng/L) and control group (1.12 ± 0.03 ng/L). There was no significant difference in serum C4 level between each group. Conclusion These results suggest that higher serum MT, IL-6, and hcy levels were correlated with pathogenesis of depression.